Pengaruh Motivisi dan Kualitas Pelayanan Terhadap Minat Mahasiswa UINSI Menjadi Nasabah Bank Sampah Syariah di UINSI Samarinda - Akhmad Shabirin; Parno Parno; Kokom Komariah (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2022)
Abstract The increasing population makes the volume of waste production also increase and varies. The amount of waste generated will have a negative impact on the environment and the economy. Therefore, the waste must be managed properly so that is becomes useful goods and has economic value. An organization that plays a role in waste management is a sharia waste bank, but in reality someone’s interest in becoming a waste bank customer does not just appear. One of them is influenced by motivation, the more motivated a person is, the greather his interest in something. Next is the quality or service, the better the service provided, the more interested someone is in something. This type of research is quantitative with a causal associative approach. The population this study were active students of UINSI Samarinda from 2018 to 2022. The sampling technique used was simple random sampling. Data collection techniques using questionnaires and documentation. The data analysis techniques are ordinal to interval data transformation (MSI), instrument test, classical assumption test, multiple linear regression analysis, coefficient of determination and hypothesis testing. Based on the results of the results of the t test it is known that motivation (X1) does not affect the interest, while the quality of service (X2) affects the interest. Simultaneously, motivation (X1) and service quality (X2) affect the interest. The coefficient of determination shows that 58.3% of the interest variables are influenced by motivation and quality, while the influence by other variables. Keywords: Motivation, Service Quality, Interest